Enhanced plastic deformation capacity in hexagonal-close-packed medium entropy alloys via facilitating cross slip. (20th January 2023) - Wen, Xiaocan; Huang, Hailong; Wu, Honghui; Zhou, Meisa; Bu, Yeqiang; Yuan, Xiaoyuan; Jiang, Suihe; Wang, Hui; Liu, Xiongjun; Wang, Hongtao; Liu, Jiabin; Wu, Yuan; et al.
Highlights: A novel Hfx (ZrTi)100-x (x=0, 20, 33 and 40 at.%) MEAs with single phase HCP was developed. Addition of Hf enhanced the strain hardening rate and tensile ductility. Effects of Hf on stacking fault energy and dislocation slip behavior were revealed. Facilitated cross slip and pyramidal dislocations is responsible for the outstanding mechanical properties. Abstract: Alloys with a hexagonal close-packed (HCP) lattice often suffer from intrinsic brittleness due to their insufficient number of slip systems, which limits their practical uses. In this paper, nevertheless, we show that remarkably tensile ductility in HCP Hf-Zr-Ti medium entropy alloys (MEAs) was achieved, particularly in the MEAs with a higher content of Hf. Both first-principles calculation and experimental analyses reveal that addition of Hf increases basal I2 stacking fault energy and decreases prismatic stacking fault energy in these HCP MEAs, which promotes the source of pyramidal dislocations due to the facilitated cross slips of basal dislocations and eventually give rise to the observed large tensile ductility. Our current findings not only shed new insights into understanding deformation of HCP alloys, but also provide a basis for controlling alloying effects for developing novel HCP complex alloys with optimized properties. Graphical abstract: Image, graphical abstract